Price-dependent demand in spatial models - Yiquan Gu; Tobias Wenzel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
This paper introduces price-dependent individual demand into the circular city model of product differentiation. We show that for any finite number of firms, a unique symmetric price equilibrium exists provided that demand functions are not too convex. As in the case of unit demand, the number of firms under free entry decreases in the fixed cost of entry while increases in the transportation cost of consumers. However, this number is no longer always in excess of the socially optimal level. Insufficient entry occurs when the fixed and transportation costs are high.
Keywords: L11; L13; R1; 330; spatial models; price-dependent demand; horizontal product differentiation; demand elasticity; excess entry theorem